Multi-material NiTi-PEEK hybrid cellular structures by selective laser melting and hot pressing: tribological characterization - Costa, M. M. (2021)
In this study, a multi-material NiTi-PEEK cellular structured solution was designed, produced and characterized targeting orthopedic applications. For that purpose, Selective Laser Melting (SLM) technique was used to produce NiTi cellular structures with different open-cell sizes and wall thicknesses. Hot Pressing (HP) technique was used to introduce PEEK in the open-cells of NiTi structures to obtain multi-material components. Morphological characterization showed that the selected SLM processing parameters were suited to achieve high-quality parts without significant defects. Tribological characterization proved an enhanced wear resistance to the multimaterial specimens when compared with the mono-material NiTi structures. These multi-material structures are a promising solution for providing a customized stiffness and superior wear resistance to NiTi structures to be integrated in innovative orthopedic designs.